2013
DOI: 10.1186/1477-7525-11-185
|View full text |Cite
|
Sign up to set email alerts
|

Use of pedometer-driven walking to promote physical activity and improve health-related quality of life among meat processing workers: a feasibility trial

Abstract: BackgroundCurrent evidence supports the use of pedometers as effective motivational tools to promote physical activity and improve health-related quality of life in the general population. The aims of this study are to examine whether a pedometer-driven walking programme can improve health-related quality of life, and increase ambulatory activity in a population of meat processing workers when compared to a control group receiving educational material alone.Methods/designA feasibility study employing a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The seriousness of work related musculoskeletal disorders were highlighted and it was also reported that the prolonged exposure to loads due to variable work intensity leads to musculoskeletal disorders [6]. The workers engaged in meat processing were studied and various activities involving repetitive movements, more application of forces, high working rate and incorrect postures for a longer duration were identified [1,10]. It was suggested that the hazards such as infection, lung cancer and knife related injuries are more evident in case of butchers [4].…”
Section: Introductionmentioning
confidence: 99%
“…The seriousness of work related musculoskeletal disorders were highlighted and it was also reported that the prolonged exposure to loads due to variable work intensity leads to musculoskeletal disorders [6]. The workers engaged in meat processing were studied and various activities involving repetitive movements, more application of forces, high working rate and incorrect postures for a longer duration were identified [1,10]. It was suggested that the hazards such as infection, lung cancer and knife related injuries are more evident in case of butchers [4].…”
Section: Introductionmentioning
confidence: 99%
“…The study outlined in this paper has been designed to determine the effectiveness of a community-based pedometer-driven walking programme as a low cost, easily accessible, and sustainable means of physical activity to improve disability and clinical outcomes for people with CLBP in a Saskatchewan context. The study design builds on the knowledge gained in recent reviews [ 14 , 19 , 22 , 62 ], prior protocol development [ 20 , 63 ] and recent walking studies [ 21 , 64 ]. Results from this study will inform future exercise-based strategies for larger comparative international clinical trials aimed at reducing disability in those suffering from CLBP as well as establishing the feasibility of pedometer-driven walking programmes in the farming population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies point to use of a variety of activities for improving QoWL. Exercises for body posture improvement (13) , walking (14) , and Hatha Yoga (15) . Hatha Yoga was mentioned in a study conducted in Australia as a method to improve flexibility, anxiety and workers' musculoskeletal development (15) .…”
Section: Physical Activities and Health Carementioning
confidence: 99%
“…Mansi, 2013 (14) New Zealand 60 workers To investigate if a walking program with use of a pedometer could improve health quality for meat processing workers…”
Section: Quantitativementioning
confidence: 99%